2020
DOI: 10.1002/sctm.19-0241
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells pretreated with pro-inflammatory cytokines promote skin wound healing through VEGFC-mediated angiogenesis

Abstract: Skin is the largest organ of the human body. Skin wound is one of the most common forms of wound. Mesenchymal stromal cells (MSCs) have been used to aid skin wound healing via their paracrine factors. Because the secretome of MSCs can be greatly enriched and amplified by treatment with IFN-γ and TNF-α (IT), we here tested whether supernatant derived from MSCs pretreated with IT, designated as S-MSCs-IT, possesses improved wound healing effect by using a murine model of cutaneous excision, S-MSCs-IT was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Vascular ingrowth is critical for successful biomaterial integration since nutrition of cells within the implant via diffusion is limited to 150–200 μm [ 28 , 29 ], and any pro-angiogenic effects are supportive. TNFα-inhibition is not commonly associated with pro-angiogenic effects; in fact, in certain environments, TNFα-stimulation has been shown to promote angiogenesis via vascular endothelial growth factor, in particular [ 30 , 31 ]. While we used Matrigel which is known for its pro-angiogenic potential as a carrier for Etanercept which is currently available for systemic application in humans, it is important to keep in mind that we used a growth-factor reduced version of Matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular ingrowth is critical for successful biomaterial integration since nutrition of cells within the implant via diffusion is limited to 150–200 μm [ 28 , 29 ], and any pro-angiogenic effects are supportive. TNFα-inhibition is not commonly associated with pro-angiogenic effects; in fact, in certain environments, TNFα-stimulation has been shown to promote angiogenesis via vascular endothelial growth factor, in particular [ 30 , 31 ]. While we used Matrigel which is known for its pro-angiogenic potential as a carrier for Etanercept which is currently available for systemic application in humans, it is important to keep in mind that we used a growth-factor reduced version of Matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…Following stimulation of TLR5-expressing cells with flagellin, a signaling cascade is triggered, which involves phosphorylation of IL-1 receptor-associated kinase 1, leading to activation of mitogen-activated protein kinase kinases and inhibitor of NF-κB kinases, ultimately activating inflammatory protein production via NF-κB and p38 mitogen-activated protein kinase ( 24 ). However, most previous studies have focused on the beneficial effects of ADSCs activated by cytokines such as TNF-α, IL-1β and IFN-γ ( 17 , 19 , 34 ). Thus, limited information is available regarding the immunomodulatory properties of flagellin-exposed ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse, rat and in vitro cell model studies, MSCs have been found to be potently angiogenic ( 192 , 212 221 ). As outlined previously, MSCs most likely promote angiogenesis via paracrine means, such as secretion of angiogenic factors; vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), transforming growth factor beta (TGF-β), and platelet-derived growth factor (PDGF) ( 222 , 223 ), which are promoted under hypoxic conditions ( 224 ).…”
Section: Msc Transplantation Could Attenuate Damage and Facilitate Rementioning
confidence: 99%